Pengaruh Pemanfaatan Teknologi Informasi, Kualitas Sdm, Dan Kebijakan Pemerintah Terhadap Kinerja Keuangan - Ali Saifudin; Munari Munari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
which can be used to support the village's financial performance, especially in the economic and health sectors, which is a milestone in the recovery after the COVID-19 pandemic. This study aims to examine the influence of information technology utilization, human resource quality, and government policies on financial performance in the COVID-19 pandemic era in Sukolilo District, Surabaya City. The sample in this study was 39 respondents determined by the Purposive Sampling technique. Data analysis conducted in this study using SmartPLS 4 software. The results of the data analysis that does not affect the financial performance, the quality of human resources influence the financial performance, and government policies does not affect the financial performance. Keywords: Technology, HR, Policy, Financial Performance